Lying Down Instability Undetected on Standing Dynamic Radiographs - Kim, Hyeun Sung (J Korean Neurosurg Soc, 2015)
It is well known that spinal instability should be evaluated in the standing lateral position. Standing dynamic flexion and extension radiographs are usually used to assess spinal instability. Here, we report a patient who experienced distraction instability while in the supine position rather than the standard standing position. To our knowledge, this is the first report of lying-down instability undetected on standing dynamic flexion and extension radiographs. We discuss the pathophysiological mechanism of this uncommon but possible entity and provide a review of the literature.